(3dhGeY GdCSQGQ aj TQM eWGdY GdCfhGQs - (3GdbWH GdQGRis; (3GdSQGL GdGQehj , eMehO Hf CHj HcQ Hf CMeO, SQGL GdOjf CHh GdKfGA,J (B682 (3g` s ((3CMeO Hf chjOc GdWGhTi s)
(3ChdgG (B:s
(3hHYO , aEf GdYdhe Ydi JTYH afhfgG s
(3BNQgG (B:s
(3hfPcQ ajgeG NhGU eJYOOI Ch CMO efgeG Ch GdYGe s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdadSaI hGdefWbs